PERAN DINAS PERDAGANGAN DAN PERINDUSTRIAN DALAM MEMAJUKAN INDUSTRI KECIL MENENGAH (IKM) DI KOTA TANJUNGPINANG TAHUN 2022 - Riyan Tika Syafitri, Riyan Tika Syafitri; Nazaki,; Ryan Anggria Pratama, (Madika: Jurnal Politik dan Governance, 2023)
Small and Medium Industries (IKM) are the most important pillars of the economy in the city of Tanjungpinang. Of course, Pemko continues to encourage local economic growth through micro, small and medium enterprises. This can be seen from the number of business units in the city of Tanjungpinang which continues to increase every year. It was recorded that in 2019-2022 there were 997 IKMs with various types of businesses including 670 food IKMs, 165 clothing IKMs, 68 crafts IKMs, and 94 other types of business IKMs. Because so far the IKM sector has proven its important role in making a significant contribution to the economy of the city of Tanjungpinang. In line with that, from 2019-2022, the number of workers who received competition-based training reached 359 people. The aim of this research is to find out the Role of the Department of Trade and Industry in Promoting Small and Medium Industries (IKM) in Tanjungpinang City in 2022 by using Ndraha Labolo's theory. The method used is a qualitative research method with as many as 7 informants and uses techniques and data collection in the form of interviews, observation and documentation. The results of this study show that the role of the Trade and Industry Office of the City of Tanjungpinang as a regulator is regulated in Mayor Regulation No. 39 of 2016 concerning Description of the Main Tasks and Organizational Functions and Work Procedures of the Office of Trade and Industry of the City of Tanjungpinang. The role played by the Trade and Industry Office of Tanjungpinang City as a dynamic in advancing the Small and Medium Industries (IKM), namely by providing training, coaching to the Small and Medium Industries (IKM) so that difficulties in obtaining business licenses and obtaining halal certificates can be resolved easily by using PTSP. The role of the Government as a facilitator for Small and Medium Industries (IKM), namely by providing promotion space for Small and Medium Industries (IKM) as well as in obtaining halal certification, the Government's Department of Trade and Industry has facilitated the issuance of halal certification from BPOM. Key Word: Advancing, Small and Medium Industries (IKM), Role.